Exploring Chinese middle-class parents’ challenges and coping strategies of dialogic reading in a digital EFL context - Zhao, Lili; Cai, Xiangli; Qin, Limin (Frontiers in Psychology, 2026)
IntroductionAgainst the backdrop of English learning enthusiasm in China, many Chinese parents are using digital storybooks to support their children’s early English as a Foreign Language (EFL) learning. While previous research has demonstrated the benefits of dialogic reading of digital storybooks, the challenges parents encounter in a non-native English speaking context are under-explored.MethodsEmploying parent–child reading videotaped recordings, reflective journals, and semi-structured interviews, this qualitative study collected data from 18 Chinese parent–child dyads over 8 weeks. Thematic analysis was used to explore parents’ challenges and coping strategies in dialogic reading.ResultsThe findings demonstrated that Chinese middle-class parents experienced two major challenges. Parent-related challenges were characterized by the self-limitation of the communicative MKO role, a conflict between high cognitive load and strategy mastery, and time constraints. Child-related challenges stemmed from a mismatch between the child’s ZPD and dialogic strategy demands, as well as attention competition in the digital environment. In response, parents utilized self-scaffolding to equip themselves as competent MKOs. Furthermore, the parents and the digital English storybooks jointly provided dual scaffolding for children’s reading and English language acquisition.DiscussionBy exploring these challenges and coping strategies, this study extends Sociocultural Theory by expanding the concepts of the MKO and Scaffolding in the digital EFL context. It also provides practical insights for parental training, dialogic reading implementation and the design of digital storybook Apps.